Make their day! : employee recognition that works : proven ways to boost morale, productivity, and profits - Ventrice, Cindy , 1956- (Berrett-Koehler Publishers, 2009)
"Companies spend billions of dollars on recognition programs each year. While recognition done right improves morale and productivity, most of the money spent is wasted because people in most organizations still don?t feel recognized. Research shows employees often want something very different from the plaques and awards most companies rely on for recognizing employee contribution. In this thoroughly updated and expanded edition of Make Their Day, author Cindy Ventrice explores how managers need to adapt their recognition strategies to deal with global, virtual, and generational realities. Additions include chapters on workplace culture, fairness, and remote communication."--BOOK JACKET